Identification of Metallothionein Gene in Human Plasma: A Molecular Analysis of Cadmium and Lead Pollution in Gas Station Environment - Dewi, N. K.; Yuniastuti, A.; Ahmed, A. M. A. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
Metallothionein (MTs) is a protein that binds to metals, cysteine-rich and has low molecular weights. Metallothionein binds metals and has some essential cellular functions, such as transportation, storage, and metal detoxification. When metallic lead (Pb) and cadmium (Cd) are absorbed, it will immediately be bounded by metallothionein and transported by the blood to the liver. Metallothionein gene is encoded by MTs. This study aimed to identify the MTs gene in blood of fuel station workers which can further be used as a biomarker of the vulnerability of the body as a result of exposure to heavy metals like Pb and Cd in humans. This study was a cross-sectional study, conducted for 8 months and took place in Fuel Stations in the city of Semarang. Samples were fuel station workers who met the study criteria, they sought to fulfill as much as 52 samples. Blood of samples was taken approximately 5 ml and then the MT2 gene was analyzed using Polymerase Chain Reaction (PCR). The data were analyzed descriptively. The results showed that 96% of MT2 gene expression had a resemblance to normal human gene sequences by Blast GenBank. MT2 gene expression does not always reflect the accumulation of lead and cadmium in the blood of fuel station workers. The MT2 gene is likely to have a limitation when used as a biomarker for early detection of the heavy metals exposure in humans to determine the susceptibility of heavy metals exposure.